Medellín: From Colonial Christianity to Liberating Christianity - Tamayo, Juan-José (2018)
The article problematizes the Medellín Conference based on the assumption that, in this event, the paradigm of a colonial Church was changed to a liberating Church. In that sense, the documents of Medellín continue to be, still today - and will be more so in the future - a good program for the renewal of ecclesial institutions. The article demonstrates that the Medellín Conference had two major impacts: in the pastoral, by renewing pastoral practices and orienting them towards the office of the basic ecclesial communities; in theology leading the Latin American Church to discover the importance of the social place of theology, a matter almost neglected until then and deemed irrelevant, since what mattered was to elaborate a formally rigorous theology.